A case report of autoimmune necrotizing myositis presenting as dysphagia and neck swelling. Issue 1 (January 2016) - Ngo, Linh; Wu, Andrew; Nguyen, Matthew; McPherson, Lauren; Gertner, Elie
Abstract Background Severe dysphagia may occur in the immune mediated necrotizing myopathies (IMNM). Neck swelling and severe dysphagia as the initial symptoms upon presentation has not been previously described. Case presentation A 55-year-old male with a 4 week history of neck swelling, fatigue, dysphagia, myalgias, night sweats, and cough was admitted for an elevated CK. He underwent extensive infectious and inflammatory evaluation including neck imaging and muscle biopsy. Neck CT and MRI showed inflammation throughout his strap muscles, retropharyngeal soft tissues and deltoids. Infectious work up was negative. Deltoid muscle biopsy demonstrated evidence of IMNM. Lab tests revealed anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) antibodies confirming the diagnosis of HMGCR IMNM. Conclusions HMGCR IMNM is a rare and incompletely understood disease process. Awareness of HMGCR IMNM could potentially lead to earlier diagnosis, treatment and improved clinical outcomes as disease progression can be rapid and severe.